Aggregation‐Induced Emission (AIE): A Historical Perspective. Issue 34 (13th July 2020) - Würthner, Frank
Abstract: Aggregation‐induced emission (AIE) has attracted considerable interest over the last twenty years. In contrast to the large number of available reviews focusing specifically on AIE, this Essay discusses the AIE phenomenon from a broader perspective, with an emphasis on early observations related to AIE made long before the term was coined. Illustrative examples are highlighted from the 20th century where fluorescence enhancement upon rigidification of dyes in viscous or solid environments or J‐aggregate formation was studied. It is shown that these examples already include typical AIE luminogens such as tetraphenylethylene (TPE) as well as stilbenes and oligo‐ or polyphenylenevinylenes and ‐ethynylenes, which became important fluorescent solid‐state materials in OLED research in the 1990s. Further examples include cyanine dyes such as thiazole orange (TO) or its dimers (TOTOs), which have been widely applied as molecular probes in nucleic acid research. The up to 10 000‐fold fluorescence enhancement of such dyes upon intercalation into double‐stranded DNA, attributable to the restricted intramolecular motion (RIM) concept, afforded commercial products for bioimaging and fluorescence sensing applications already in the early 1990s. Abstract : An old phenomenon in a new light : In this brief Essay, the currently highly recognized aggregation‐induced emission (AIE) phenomenon is discussed in a broader perspective by illustrating its roots in earlier work.